Poly- and perfluoroalkyl substances exposure during pregnancy and postpartum depression: Evidence from the Shanghai birth cohort. (March 2023) - Wang, Hui; Ren, Tai; Zhang, Na; Xia, Weiping; Xiang, Mi; Ran, Jinjun; Zhang, Jun
Abstract: Background: Exposure to poly-and perfluoroalkyl substances (PFASs) has been linked to psychiatric disorders in the general population. Because women in the postpartum period are susceptible to mental disorders, we aimed to investigate the association between exposure to PFASs during pregnancy and postpartum depression (PPD). Methods: Our study consisted of 2741 pregnant women who were enrolled in the Shanghai Birth Cohort during the early pregnancy and gave birth to a singleton live birth between 2013 and 2016. A total of 10 PFASs were measured in maternal plasma collected in early gestation by high-performance liquid chromatography/tandem mass spectrometry. PPD was assessed using the Edinburgh Postnatal Depression Scale (EPDS) at 42 days after the child birth. We used multivariable logistic regression to estimate the association between exposure to PFASs and PPD, adjusted for potential confounders. Negative binomial regression was used to assess the association between PFASs exposure during pregnancy and EPDS subscales including anhedonia, anxiety, and depression. A quantile-based g-computation approach was used to evaluate the joint and independent effects of PFASs on PPD. Results: Around 11.7% of the mothers had probable PPD (EPDS cut-off ≥10). Overall, exposure to PFASs in early pregnancy was not associated with PPD or EPDS subscales. Quantile g-computation method also showed that increasing PFASs mixture by one quartile was not associated with PPD (odds ratio, 1.08; 95% confidence interval: 0.91, 1.29). Conclusion: Our findings indicate that exposure to PFASs during pregnancy was not associated with PPD at 6 weeks postpartum. Graphical abstract: Image 1 Highlights: Our study consisted of 2741 pregnant women who were enrolled in the Shanghai Birth Cohort. Ten PFASs were measured in maternal plasma collected at the first-trimester prenatal visit. G-computation approach was used to evaluate the joint and independent effects of PFASs on postpartum depression. Exposure to PFASs during pregnancy was not associated with postpartum depression.